ROBOTIC AND EXOSKELETON-ASSISTED GAIT TRAINING IN POST-STROKE REHABILITATION: A SYSTEMATIC REVIEW - Paulina Łobaza,; Idalia Myszor,; Michał Madej,; Maria Kubacka,; Lucjan Kocemba,; Gabriela Mroczka,; Sylwia Nycz-Jucha,; Brygida Pinkowicz,; Piotr Rachwał,; Barbara Nowak-Misiąg, (International Journal of Innovative Technologies in Social Science, 2025)
Robotic and exoskeletal gait assistance systems are becoming an increasingly important part of post-stroke rehabilitation, offering the possibility of more intensive, repetitive and individualised locomotion training than traditional methods.The review analysed 15 studies published between 2015 and 2024. The review included studies in which an exoskeleton or gait assistance robot was the main therapeutic intervention, and the analysis was narrative and systematic.The results of the studies indicate that interventions using exoskeletons can lead to improvements in walking speed and quality, stride length, balance and lower limb motor function. The benefits were particularly evident in the subacute phase after stroke, and some of the studies also reported changes indicative of beneficial neurophysiological reorganisation. The therapy proved to be safe and well tolerated, and patients showed high acceptance and motivation to participate in the sessions. The limitations of the analysed studies included small sample sizes, varied treatment protocols and a lack of long-term follow-up.The evidence suggests that robotic gait training is a valuable addition to conventional rehabilitation, but larger, well-designed studies are needed to more accurately assess the effectiveness and optimal use of these technologies. Designed studies are needed to more accurately assess the effectiveness and optimal use of these technologies.Materials and Methods: A literature review was conducted using the PubMed database, covering publications from 2015 to 2024, a period of particularly dynamic development of robotic and exoskeletal methods of gait rehabilitation after stroke. Keywords were used in the search. Based on an analysis of titles and abstracts, studies on the use of exoskeletons in gait training in stroke patients were selected. Fifteen studies meeting the substantive criteria, including randomised controlled trials, pilot projects and feasibility studies, were included in the final review [10-24]. Data on population characteristics, the therapeutic protocol used, assessment tools, clinical outcomes, and information on the tolerance and safety of the therapy were obtained from each study. The review methodology was narrative and systematic; the aim was not to create a meta-analysis, but to provide a synthetic overview of the available results, compare the therapeutic approaches used, and identify research gaps. This allowed us to capture both the strengths of the technology, such as safety and high patient acceptance, and its limitations, including small study samples, heterogeneity of protocols, and lack of long-term data.